The cities of Narovchat, Krasnoslobodsk and Troitsk as centers of interethnic integration processes in the Primokshan region 16th – 17th centuries - V.I. Pervushkin (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки, 2024)
Background. The resettlement of Russians outside the original borders of the Mos-cow state and the accession of new lands to it on this basis is a very topical topic of modern research. However, local territories, in particular Primokshan region, were not actually sub-jected to detailed study. This problem is fundamental in understanding the formation of the Russian people and the role of cities in accelerating interethnic integration processes. Materials and methods. Observingthe principle of historicism, using the method of analysis and synthesis using the local method of research, the author analyzes written sources and works of histori-ans of the 19th–21st centuries. Results. Documentary sources and factual material of special studies of Soviet and Russian historians are analyzed. Some features that influenced the inter-ethnic integration processes in Primokshan region are noted, in particular, among the Russian service people there is a significant percentage of foreigners – Mordovians and Tatars – in-volved in protecting the borders of the Russian state. These processes were also influenced by the construction of “location features”, monasteries and churches. Conclusions. In the process of forming the territory of Russia as a multinational state, we highlight such a feature as the construction of the cities of Narovchat, Krasnoslobodsk and Troitsk, which were ac-celerators of ethnic and ethno-cultural processes aimed at integrating their population. With the fall of Kazan, the main specificity of interethnic integration processes in Primokshan region is their initiation from above. The Christianization of non-Russian peoples made sig-nificant changes in the process of formation of the Russian nationality, which was reflected in the dialectical features of the language of the Russian population of Primokshan region.